Preparation and Characterization of Liquid Crystalline Polyurethane/Al2O3/Epoxy Resin Composites for Electronic Packaging - Shaorong Lu; Jianfeng Ban; Kuo Liu (International Journal of Polymer Science)
Liquid crystalline polyurethane (LCPU)/Al2O3/epoxy resin composites were prepared by using LCPU as modifier. The mechanical properties, thermal stability, and electrical properties of the LCPU/Al2O3/epoxy resin composites were investigated systematically. The thermal oxidation analysis indicated that LCPU/Al2O3/epoxy resin composites can sustain higher thermal decomposition temperature. Meanwhile, coefficient of thermal expansion (CTE) was also found to decrease with addition of LCPU and nano-Al2O3.